Serological evidence and factors associated to liver damage in malaria-typhoid infected patients consulting in two health facilities, Yaoundé-Cameroon - Madeleine Yvanna Nyangono Essam; Arnaud Fondjo Kouam; Armelle Gaelle Kwesseu Fepa; Armel Jackson Seukep; Elisabeth Menkem Zeuko’o; Felicité Syntia Douanla Somene; Nembu Erastus Nembo; Paul Fewou Moundipa; Frédéric Nico Njayou (PLoS ONE, 2025)
Malaria and typhoid fever remain major health issues in developing countries like Cameroon, with frequent co-infections. The potential liver damage caused by their respective causative pathogens is overlooked in health management, posing a significant risk of severe liver injury and worsening patient conditions. Accordingly, this study investigated the risk factors associated with liver damage in febrile patients with malaria, typhoid fever, or co-infection at the Obili District Medical Center and Mvog-Betsi Dominican Hospital Center, Yaoundé, Cameroon. Over 8 months, 350 febrile patients were evaluated for their adherence to preventive measures concerning malaria and typhoid fever using a structured questionnaire. Blood samples were analyzed for Plasmodium species and Salmonella antibodies and liver enzyme levels were measured. Liver damage was assessed using the Roussel Uclaf Causality Assessment Method. Risk factors for infections and liver damage were identified using Fisher’s Exact and Chi-Square tests, with significance set at P < 0.05. Among participants tested, 129 (36.86%) and 106 (30.29%) were positive for malaria and typhoid, respectively, while 56 (16.00%) were co-infected. Men (49.2% and 37.3%) were more affected than women (30.6% and 26.7%) for both malaria and typhoid, respectively. Participants aged between 20 and 40 years were the most affected by malaria (21.4%) and typhoid fever (17.4%). The non-use of mosquito nets, presence of standing water, bushes, and garbage dumps near residences were significant risk factors (Relative risk: RR > 2.1; P < 0.0001) for contracting malaria or typhoid fever. The co-infection status (Chi-2 = 18.30; P < 0.0001), parasite density (Chi-2 = 9.8; P = 0.0074), and delay before consulting (Chi-2 = 13.23; P = 0.0013) were significant risk factors for the occurrence of liver injuries. Our findings demonstrated that the alteration of liver enzyme activity, reflecting liver damage among patients with malaria, typhoid, or malaria-typhoid co-infection, is a reality and should be considered during the patient treatment.